(untitled) (Gestionar: revista de empresa y gobierno, 2021)
An analysis of the main macroeconomic variables that influence gold exports in Peru, period 2000 - 2015. Likewise, it seeks to determine the elasticities of gold exports against the variations of the main macroeconomic variables that influence gold exports. The Pesaran cointegration econometric model was used. It was found that the elasticities of gold exports against the Gross Domestic Product are 5.04%, 0.82%, and 6.99% for Switzerland, Canada, and the United States, respectively. Furthermore, the terms of trade have had a significant impact on the central destination countries. For example, being cheerful and elastic for the Swiss and United States markets with 0.004% and 0.03% respectively, and negative for the Canadian market with -1.09%. These results can be used to improve the economic policies of international trade for the exporting companies of mining products in the country.